Із історії кафедри математичної фізики (до 110 річниці НТУУ «КПІ») - Добровольська, Е.М.; Авдєєва, Т.В. (Питання історії науки і техніки, 2008)
Статья представляет очерк преподавания и развития математических исследований, проведенных многими сотрудниками кафедры математической физики за последние два десятилетия. The article represents an essay of teaching and development of the mathematical researches
were leading by many employees of faculties of mathematical physics of the Kiev
polytechnic institute for the last two decades.